Development Of A Hybrid Energy Greenhouse Solar Dryer With A Vertical Rotating Rack System For Drying Fish - Yahya, Muhammad; Wardianto, Dedi (IJIMCE : International Journal of Innovation in Mechanical Construction and Energy, 2025)
This study aimed to evaluate the performance of a greenhouse solar dryer with a vertical rotating rack system (GHSD-VRR), integrated with an air recirculation system and a biomass furnace with air preheater. This GHSD-VRR was able to reduce the weight of fish from 88.6 kg with a wet basis moisture content of 68.5% (2.18% on a dry basis) to 34.4 kg with a wet basis moisture content of 20% (0.21% on a dry basis) at an average air temperature of about 57.0°C and an average sunlight of 629 W/m² in 10.8 hours. The average drying rate (DR) and specific moisture extraction rate (SMER) reached 4.44 kg/s and 0.211 kg/kWh, respectively. The average specific energy consumption (SEC), specific thermal energy consumption (STEC), and specific electrical energy consumption (SEEC) were 7.724 kWh/kg, 6.408 kWh/kg, and 1.315 kWh/kg, respectively. The efficiency of biomass furnace, dryer, and exergy were recorded at 66.9%, 38.7%, and 80.5%, respectively. The contribution of heat energy from sunlight and biomass to the dryer system was 19.18% and 64.7%, respectively.